THE INFLUENCE OF DIGITAL MARKETING AND ELECTRONIC WORD OF MOUTH TO PURCHASE INTENTION - Antarizkia, Ryan; Arif, Moh. Erfan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The increasing development of technology and the easier it is to access the internet make the digital world nowadays more and more popular. For companies, social media has become a new tool as a form of marketing strategy to convey messages, get feedback and also communicate directly with their consumers. This study was purposed to determine the effect of digital marketing and electronic word of mouth to purchase intention. This study is explanatory research which explains the connection between research variables through hypothesis testing. The sampling technique used purposive sampling method. The sample size used were 108 respondents with the provision that they have been the school yearbook committee and know Ritual Project through social media. The data analysis technique used in this study was multiple regression with SPSS statistical software. Based on the results of the testing, it can be concluded that digital marketing has a significant influence on purchase intention and electronic word of mouth has a significant influence on purchase intention.